Evaluation of Groundwater Hydrochemistry in Altun Kopri Basin, NE Iraq - Akbar, Mustafa J.; Al-Shamma’a, Ayser M. (Iraqi Journal of Science, 2025)
The study area is located in the northeastern part of Kirkuk Governorate, Iraq, and its goal is to assess the hydrochemical characteristics of groundwater, identify contamination levels and sources, and determine groundwater suitability for drinking. The water quality index (WQI) and heavy metals pollution index (HPI) were used to assess groundwater contamination levels of major elements and heavy metals. The results showed that all groundwater samples were alkaline and weakly mineralized water. The total dissolved solids in the groundwater were less than the maximum accepted limit for palatable water. Groundwater was classified as excellent to good water and does not exceed the critical drinking water value. Chemically, All indices indicate that the groundwater in the study area is suitable for drinking water. Finally, the authors recommend that groundwater needs a biological assessment to make a relevant decision about water suitability for drinking.